1995
DOI: 10.1073/pnas.92.5.1699
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of a minimal functional transactivation domain from the human glucocorticoid receptor.

Abstract: A 58-amino acid polypeptide containing the functional core region, the x1 core, of the major transactivation domain of the human glucocorticoid receptor has been expressed in Escherichia coli and purified to homogeneity. The polypeptide retains 60-701% ofthe activity ofthe intact domain when assayed in vivo or in vitro. This report describes a structural characterization of the T1 core peptide fragment. Circular dichroism spectroscopy shows that the T1 core and a larger fragment encompassing the intact Tl doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
144
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(156 citation statements)
references
References 38 publications
10
144
1
Order By: Relevance
“…The amino-terminal activation Region I appears to contribute little to the backbone and tertiary structure of N . In isolation, the Region I peptide was structured with respect to helix and sheet, in contrast to observations consistently made for activation domains of eukaryotic transcription factors (for example Dahlman-Wright et al, 1995). A lack of intrinsic conformational preference of the Region I peptide would indicate that a particular Region I secondary structure within N could be directed by tertiary interactions between Region I and other parts of N .…”
Section: Discussioncontrasting
confidence: 63%
“…The amino-terminal activation Region I appears to contribute little to the backbone and tertiary structure of N . In isolation, the Region I peptide was structured with respect to helix and sheet, in contrast to observations consistently made for activation domains of eukaryotic transcription factors (for example Dahlman-Wright et al, 1995). A lack of intrinsic conformational preference of the Region I peptide would indicate that a particular Region I secondary structure within N could be directed by tertiary interactions between Region I and other parts of N .…”
Section: Discussioncontrasting
confidence: 63%
“…Independent experiments have shown that substitution of the ␣-helixbreaking amino acid proline for natural residues at critical positions in these putative helices significantly reduces the transcriptional potency of the GR (17). Other experiments have shown that mutations of the hydrophobic amino acids in AF1 reduce both its interactions with other coregulatory proteins and its transactivation function (21).…”
mentioning
confidence: 97%
“…It has been reported that in the presence of trifluoroethanol, the ''core'' of AF1 (AF1 c , amino acids 187-242), located toward the C-terminal end of AF1, adopts three helical segments (17). Independent experiments have shown that substitution of the ␣-helixbreaking amino acid proline for natural residues at critical positions in these putative helices significantly reduces the transcriptional potency of the GR (17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mutants: Circular Dichroism-TFE is known to induce helical secondary structure in proteins that contain unordered structures and have potential for developing helixes under a hydrophobic environment (41,42). Since the long F-domain in HNF-4␣ molecule is random coil-proline-rich with very low helix content (22,38), the potential of the three forms of HNF-4␣ to form helix structure in the presence of TFE and the influence of F-domain were examined (Fig.…”
Section: Effect Of Trifluoroethanol (Tfe) On Secondary Structure Of Fmentioning
confidence: 99%